2020
DOI: 10.1097/md.0000000000019364
|View full text |Cite
|
Sign up to set email alerts
|

A clinical prediction rule for acute bilirubin encephalopathy in neonates with extreme hyperbilirubinemia

Abstract: To establish a clinical prediction rule for acute bilirubin encephalopathy (ABE) in term/near-term neonates with extreme hyperbilirubinemia. A retrospective cohort study was conducted between January 2015 and December 2018. Six hundred seventy-three out of 26,369 consecutive neonates with extreme hyperbilirubinemia were enrolled in this study. Data included demographic characteristics, total serum bilirubin (TSB), albumin, bilirubin/albumin ratio (B/A), direct antiglobulin test, glucose-6-phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(23 reference statements)
0
9
1
Order By: Relevance
“…Moreover, the early diagnosis of BE is important for physicians to make effective decisions before appearance of the symptoms and to subsequently reduce the morbidity and mortality of the disease ( 4 ). Several other studies have discussed the potential diagnostic value of some biomarkers for the early diagnosis of BE ( 1 , 6 , 16 , 17 ). In our study, we performed ROC analysis, and the results indicated that either IL-1β or TGF-β could distinguish BE patients from healthy controls with a high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the early diagnosis of BE is important for physicians to make effective decisions before appearance of the symptoms and to subsequently reduce the morbidity and mortality of the disease ( 4 ). Several other studies have discussed the potential diagnostic value of some biomarkers for the early diagnosis of BE ( 1 , 6 , 16 , 17 ). In our study, we performed ROC analysis, and the results indicated that either IL-1β or TGF-β could distinguish BE patients from healthy controls with a high specificity and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria used for exclusion were: neonates who died within 12 h after birth, neonates with incomplete data and information, those with intracranial infection, congenital malformation (chromosome abnormality), and family history of deafness. Severe hyperbilirubinemia: total serum bilirubinemia (TSB) >342 μmol/L; very severe hyperbilirubinemia >427 μmol/L; bilirubin encephalopathy: apart from TSB>342 ( 1 ). There were typical symptoms of nervous system disorders, such as lethargy, convulsion, dystonia, and asthenia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the predictive effect was considered to be unsatisfactory (11,12). A recent study reported a predictive model that included three factors (TSB, bilirubin/albumin ratio, and sepsis) in the risk assessment of ABE (18), but further clinical validation is needed. Furthermore, the scores obtained by this prediction model cannot be directly converted into the prediction probability, which may cause confusion for users.…”
Section: Discussionmentioning
confidence: 99%
“…The bilirubin/albumin ratio is used as a surrogate for plasma-free bilirubin because it contains two of the three factors (TSB, albumin, and albumin binding affinity) that determine plasma-free bilirubin (25). However, whether bilirubin/albumin ratio can improve the prediction over TSB alone remains controversial (17,18). We think that it is more reasonable to analyze the effect of albumin on ABE in the prediction model already included in TSB.…”
Section: Discussionmentioning
confidence: 99%